Who owns you? : the corporate gold-rush to patent your genes - Koepsell, David R. (David Richard) (Blackwell public philosophy., 2009)
Who Owns You? is a comprehensive exploration of the numerous philosophical and legal problems of gene patenting.; Provides the first comprehensive book-length treatment of this subject.; Develops arguments regarding moral realism, and provides a method of judgment that attempts to be ideologically neutral.; Calls for public attention and policy changes to end the practice of gene patenting.